2016
DOI: 10.14740/jocmr2492w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Changes in Hemoglobin A1c and Body Weight During Treatment of Type 2 Diabetes With Ipragliflozin: Interim Analysis of the ASSIGN-K Study

Abstract: BackgroundIpragliflozin is a selective sodium glucose co-transporter 2 (SGLT2) inhibitor that blocks glucose reabsorption in the proximal tubules. SGLT2 inhibitors are expected to be effective in patients with insulin resistance and obesity, but it is important to select treatment according to patient background factors that minimizes the risk of adverse events. There have been a limited number of investigations into the relationship between the clinical efficacy (reducing hemoglobin A1c (HbA1c) and body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 12 publications
3
26
2
1
Order By: Relevance
“…In the present study, the mean HbA1c levels at baseline (60 mmol/mol (7.6%) and 57 mmol/mol (7.4%)) were lower than those in previous studies, in which baseline levels were closer to 69 mmol/mol (8.5%) . The absolute reduction in HbA1c by antidiabetic agents, including ipragliflozin and sitagliptin, has been shown to be lower in patients who have relatively low baseline HbA1c levels . The proportion of participants with a decrease in HbA1c levels of ≥0.5% would have been closer to our estimations if the baseline HbA1c levels for inclusion in the study had been higher.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In the present study, the mean HbA1c levels at baseline (60 mmol/mol (7.6%) and 57 mmol/mol (7.4%)) were lower than those in previous studies, in which baseline levels were closer to 69 mmol/mol (8.5%) . The absolute reduction in HbA1c by antidiabetic agents, including ipragliflozin and sitagliptin, has been shown to be lower in patients who have relatively low baseline HbA1c levels . The proportion of participants with a decrease in HbA1c levels of ≥0.5% would have been closer to our estimations if the baseline HbA1c levels for inclusion in the study had been higher.…”
Section: Discussioncontrasting
confidence: 77%
“…9,10 The absolute reduction in HbA1c by antidiabetic agents, including ipragliflozin and sitagliptin, has been shown to be lower in patients who have relatively low baseline HbA1c levels. 11,12 The proportion of participants with a decrease in HbA1c levels of ≥0.5%…”
Section: Discussionmentioning
confidence: 99%
“…Greater weight loss was associated with several patient characteristics, including absence of a history of heart failure or hypertension, use of insulin, use of GLP-1 agonist and non-use of a sulphonylurea, but the mechanism for the greater percentage reduction in weight loss in these patients was not apparent. Similarly unclear was the reason why weight reductions in this study and a previous report 30 were greater among those with lower baseline HbA1c levels at 3 months-the opposite might have been anticipated, as renal excretion of glucose and calories with SGLT2 inhibition would be lower among those with well-controlled glycaemia. 31 The observed differences in weight reduction between eGFR subgroups were not linearly associated with renal function as might have been expected.…”
Section: Discussioncontrasting
confidence: 53%
“…A pooled analysis of the effect of dapagliflozin on cardiovascular risk factors according to eGFR confirmed the decreased efficacy in reducing HbA1c among patients with eGFR ≥45 to <60 mL/min/1.73 m 2 compared with those with eGFR ≥60 to <90 or ≥ 90 mL/min/1.73 m 2 (interaction P < .001), with no influence on the effect of treatment on body weight . Finally, an interim analysis of the ASSIGN‐K study showed no relationship between sex and weight loss in Japanese patients with T2DM …”
Section: Discussionmentioning
confidence: 86%